2022
DOI: 10.31620/jccc.06.22/10
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Electronic Word of Mouth (Ewom) Communication on Purchase Intention: A Quantitative Approach

Abstract: In the digital age, electronic word-of-mouth (eWOM) communication has grown to be the most powerful influence on customer behaviour. However, the growing body of evidence raises concerns about credibility and eWOM quality. Various factors related to the source, message, medium and receiver of eWOM were collected by an extensive literature review. Aiming to synthesise existing research, this study seeks to determine the factors that contribute to eWOM's success as a wholesome construct. It also operationalises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the context of digital-marketing adoption intention (Haldar, 2022), a positive attitude of start-up company owners and managers will lead to higher chances of adoption of digital marketing (Chakraborti et al, 2022;Saini et al, 2022). On the contrary, a negative attitude toward digitalmarketing tools and technologies (Purohit et al, 2022) will lower the chances of adoption (Rani et al, 2022). Hence, we hypothesize: H 3b : RA has a negative association with ATT.…”
Section: Reasons For Adoption Reasons Against Adoption Attitude and A...mentioning
confidence: 91%
“…In the context of digital-marketing adoption intention (Haldar, 2022), a positive attitude of start-up company owners and managers will lead to higher chances of adoption of digital marketing (Chakraborti et al, 2022;Saini et al, 2022). On the contrary, a negative attitude toward digitalmarketing tools and technologies (Purohit et al, 2022) will lower the chances of adoption (Rani et al, 2022). Hence, we hypothesize: H 3b : RA has a negative association with ATT.…”
Section: Reasons For Adoption Reasons Against Adoption Attitude and A...mentioning
confidence: 91%
“…Electronic word-of-mouth is a system containing messages about products or services through online boards [18]. e-WOM is informal contact with consumers through the internet about the uses or qualities of specific goods and services or a particular seller [19]. It is a helpful marketing and communication instrument since information can spread rapidly through e-WOM [20].…”
Section: Electronic Word Of Mouth (E-wom)mentioning
confidence: 99%
“…Cronbach's Alpha and Composite Reliability were used to conduct the reliability test [29]. Cronbach's Alpha and Composite Reliability must be greater than 0.7 for the study to be considered reliable [19] [33]. Therefore, all research instruments may be reliable from the data shown above.…”
Section: Validity Convergent and Reliability Testmentioning
confidence: 99%
“…EWOM is a multi-dimensional construct that comprises quality/usefulness, quantity/intensity, positive valence, negative valence, and recency characteristics (Cheung et al, 2008;Goyette et al, 2010). Despite this, many studies examined EWOM as a single construct without evaluating the unique effect of each dimension on purchase intention (Chatterjee et al, 2022;Garg & Kumar, 2021;Prasad et al, 2019;Rani et al, 2022;Reza Jalilvand & Samiei, 2012;Sulthana & Vasantha, 2019). On the other hand, many studies included EWOM credibility as a dimension of EWOM (Al-Haddad et al, 2022;Bilal et al, 2022), making the effect of EWOM characteristics on EWOM credibility unclear.…”
Section: Introductionmentioning
confidence: 99%